The Preferences of Gen Z for Food Delivery Services: A Comparative Study of Zomato and Swiggy in Ahmedabad - Mohammed Zaid Saiyed; Manushi Desai; Jignesh Vidani (MultiTech Publisher, 2024)
This study investigates the relationship between age and various factors influencing consumer behavior towards food delivery platforms like Zomato and Swiggy. Using data collected from consumers across different age groups, the study explores how preferences for customer support, packaging quality, delivery time, offers, and platform choice are shaped by age. The analysis reveals that younger consumers are more influenced by discounts and offers, while older consumers prioritize reliability and timely delivery. The findings suggest that food delivery companies should adopt age-based segmentation to better cater to the diverse needs of their customer base. Specifically, younger consumers prefer quick deliveries and interactive digital features, while older consumers value ease of use, customer support, and dependable service. Additionally, the study highlights the importance of personalized marketing strategies, with younger users responding more to app-based promotions and older users benefiting from simplified services. The research contributes to the understanding of consumer behavior in the digital age, providing practical recommendations for improving customer engagement and satisfaction. By tailoring marketing campaigns, service offerings, and support systems to different age groups, food delivery platforms can enhance the overall consumer experience, boost loyalty, and achieve sustainable growth. The study also suggests several avenues for future research, including exploring the impact of other demographic factors, technological advancements, and geographic influences on food delivery behavior